Research Methodologies for Beginners, 1st edition - Kitsakorn, Locharoenrat (Jenny Stanford Publishing, 2020)
This textbook introduces the general points of view of research methodology in the scientific and engineering fields of studies and presents an overview of the technical and professional communication needed for article publication in journals. It comprises several practice exercises that will give beginners the confidence to move on the communicative activities. Every chapter provides problem sets that will help readers check their understanding of each concept. The book will also help readers formulate specific research topics, research questions, and hypotheses; conduct literature reviews relevant to the research topics; develop applicable research methodologies; and write and present their research outlining the key elements of the proposed projects. It is very useful for students and researchers opting for a course on research methodology and for seminars at undergraduate and graduate levels.